EVALUATION OF HEAT-TREATED TOMATO SEEDLINGS AS AN ECO-FRIENDLY INSECTICIDE OF THE RICE WEEVIL, SITOPHILUS ORYZAE - Fatma H. Galal; Haifa A.S. Alhathloul; Mohamed Hamza; AlaaEddeen M. Seufi (Journal of Animal and Plant Sciences, 2025)
Solanum lycopersicumL., or tomatoes, are cultivated and consumed all over the year and are regarded as the second-most significant crop in the world. S. lycopersicum is vulnerable to insect pests, and to extreme climatic fluctuations including heat-stress. In the current study, chemical composition and insecticidal effect was investigated in the leaves of heat-shocked S. lycopersicum seedlings. Tomato seedlings were subjected to heat shock at 40 ̊C; (HS) in comparison to control at 22 ̊C; (Con). Under the two heat regimens, leaves were extracted by ethanol. The levels of secondary metabolites (SMs) using gas chromatography-mass spectrometry (GC-MS), and insecticidal activity against the rice weevil, Sitophilus oryzae using fumigation assay were measured. Data were statistically manipulated. For Con and HS, GC-MS tests identified 11 and 18 molecules, respectively. Additionally, responses of tomato plant to heat shock (HS) resulted in more SMs compounds than in the case of control plants (Con). Out of 18 compounds, 13 were detected in HS but not in Con extracts. HS extract showed more insecticidal activity (100% mortality at 5000 ppm at day 1) than Con extract (60% mortality at 5000 ppm at day 1) against S. oryzae using fumigation assay. Strong positive correlation between mortality and concentration (R2= 0.95) was demonstrated. LC50’s were estimated at 1-, 2- and 3-days post-exposure (DPE). Based on LC50 values, HS extract exhibited more activity (39.52 and 26.85 ppm) than Con extract (1687.82 and 208.61 ppm) at 1 and 2 DPE, respectively. However, the difference was insignificant at 3 DPE (10.79 for HS and 11.08 for Con). The insecticidal effect was attributed to the bioactive compounds identified by GC-MS (methyl ketones and phthalic acid esters). Both Con and HS extracts could be regarded safer substitution of the conventional hazardous insecticides against S. oryzae, and candidates for IPM programs, too. Additional research is recommended to reveal issues related to the potential environmental impacts, human and animal health, method of application, mode of action and the pathway of tomato leaf extracts, as well.
Keywords: Solanum lycopersicum; tomatoes; climatic changes; secondary metabolites; heat shock; insecticidal activity